MC listening questions vs. integrated listening-to-summarize tasks: What listening abilities do they assess?. (April 2021) - Rukthong, Anchana
Abstract: Integrated listening-to-summarize (LTS) tasks and multiple-choice (MC) questions are two formats frequently used in combination in a language test. However, it remains somewhat unclear what abilities are assessed by these formats and, particularly, to what extent they assess language abilities required in real-life communication. In response to this issue, this study conceptualized language abilities as processes test-takers used to successfully complete the tests and investigated the listening processes used to complete the two formats, MC listening questions and LTS tasks. Twenty-four Thai university participants completed the test items and took part in a stimulated recall immediately after completing each item. Their responses were scored for performing levels and the stimulated-recall data were analysed for listening processes. The results showed that while successful completion of the MC format relied mainly on cognitive processing at the lower level, i.e., word recognition and parsing, the LTS tasks engaged successful listeners at the higher-level. Some strategies important in real-life listening were used for the LTS tasks but not for the MC items. Although supporting the continued use of MC format for language assessment, this study emphasizes that listening integrated tasks are important for assessing language abilities used in a non-testing context.